Behavioral alterations in autism model induced by valproic acid and translational analysis of circulating microRNA. (May 2018) - Hirsch, Mauro Mozael; Deckmann, Iohanna; Fontes-Dutra, Mellanie; Bauer-Negrini, Guilherme; Della-Flora Nunes, Gustavo; Nunes, Walquiria; Rabelo, Bruna; Riesgo, Rudimar; Margis, Rogerio; Bambini-Junior, Victorio; Gottfried, Carmem
Abstract: Autism spectrum disorder (ASD) is characterized by difficulties in social interaction, communication and language, and restricted repertoire of activities and interests. The etiology of ASD remains unknown and no clinical markers for diagnosis were identified. Environmental factors, including prenatal exposure to valproic acid (VPA), may contribute to increased risk of developing ASD. MicroRNA (miRNA) are small noncoding RNA that regulate gene expression and are frequently linked to biological processes affected in neurodevelopmental disorders. In this work, we analyzed the effects of resveratrol (an antioxidant and anti-inflammatory molecule) on behavioral alterations of the VPA model of autism, as well as the levels of circulating miRNA. We also evaluated the same set of miRNA in autistic patients. Rats of the VPA model of autism showed reduced total reciprocal social interaction, prevented by prenatal treatment with resveratrol (RSV). The levels of miR134–5p and miR138–5p increased in autistic patients. Interestingly, miR134–5p is also upregulated in animals of the VPA model, which is prevented by RSV. In conclusion, our findings revealed important preventive actions of RSV in the VPA model, ranging from behavior to molecular alterations. Further evaluation of preventive mechanisms of RSV can shed light in important biomarkers and etiological triggers of ASD.